The impacts of social media advertisements on millennial's consumption - Izian Idris, *; Siti Suhana, A. *; Ahmad, A.; Wong, Christine Mei Kee (The Mattingley Publishing Co., Inc, 2020)
Social media is increasingly being used as a platform to conduct marketing and advertising activities. Organizations spent a lot of money on social media ads to turn prospects into actual consumers. However, some might face the challenge of designing effective social media advertising in order to motivate consumers to purchase the advertised product. Hence, this study aims to examine the factors that might affect the effectiveness of social media advertising in order to enhance Malaysian Millennials‟ purchase intention. Quantitative research method is adopted to enable larger sample size of Millennials in Malaysia through convenience sampling. Data from a total of 200 respondents were collected to ensure that the results are accurate and minimize the non-response rate. The proposed conceptual model is based on findings of previous studies and the hierarchy of effects model theory. Findings in this study indicated there are 4 factors (advertising appeal, informativeness, perceived relevance and emotional-based evaluation) that have positive influence on Malaysian Millennial‟s intention to purchase the advertised product. This study will hopefully provide some insights for the advertising industry and marketers in Malaysia to effectively plan and implement their ads over the social media platform.